Variably protease-sensitive prionopathy: A new sporadic disease of the prion protein - Zou, Wen-Quan; Puoti, Gianfranco; Xiao, Xiangzhu; Yuan, Jue; Qing, Liuting; Cali, Ignazio; Shimoji, Miyuki; Langeveld, Jan P.M.; Castellani, Rudy; Notari, Silvio; Crain, Barbara; Schmidt, Robert E.; et al. (Annals of neurology, 2010)
Objective: The objective of the study is to report 2 new genotypic forms of protease‐sensitive prionopathy (PSPr), a novel prion disease described in 2008, in 11 subjects all homozygous for valine at codon 129 of the prion protein (PrP) gene (129VV). The 2 new PSPr forms affect individuals who are either homozygous for methionine (129MM) or heterozygous for methionine/valine (129MV). Methods: Fifteen affected subjects with 129MM, 129MV, and 129VV underwent comparative evaluation at the National Prion Disease Pathology Surveillance Center for clinical, histopathologic, immunohistochemical, genotypical, and PrP characteristics. Results: Disease duration (between 22 and 45 months) was significantly different in the 129VV and 129MV subjects. Most other phenotypic features along with the PrP electrophoretic profile were similar but distinguishable in the 3 129 genotypes. A major difference laid in the sensitivity to protease digestion of the disease‐associated PrP, which was high in 129VV but much lower, or altogether lacking, in 129MV and 129MM. This difference prompted the substitution of the original designation with “variably protease‐sensitive prionopathy” (VPSPr). None of the subjects had mutations in the PrP gene coding region. Interpretation: Because all 3 129 genotypes are involved, and are associated with distinguishable phenotypes, VPSPr becomes the second sporadic prion protein disease with this feature after Creutzfeldt‐Jakob disease, originally reported in 1920. However, the characteristics of the abnormal prion protein suggest that VPSPr is different from typical prion diseases, and perhaps more akin to subtypes of Gerstmann‐Sträussler‐Scheinker disease. ANN NEUROL 2010;68:162–172